Iron Metabolism and Brain Development in Premature Infants - Wang, Yafeng; Wu, Yanan; Li, Tao; Wang, Xiaoyang; Zhu, Changlian (Frontiers in Physiology, 2019)
Iron is essential for a remarkable array of critical functions during brain development, and it needs to be supplied in adequate amounts, especially to preterm infants. This review article provides an overview of iron metabolism and homeostasis at the cellular level, as well as its regulation at the mRNA translation level, and we emphasize the importance of iron for brain development in fetal and early life in preterm infants. We also review the risk factors for disrupted iron metabolism that lead to high risk of developing iron deficiency and subsequent adverse effects on neurodevelopment in preterm infants. At the other extreme, iron overload, which is usually caused by excess iron supplementation in iron-replete preterm infants, might negatively impact brain development or even induce brain injury. Maintenance of iron homeostasis is essential during the fetal and neonatal period, and thus iron status should be monitored routinely and evaluated thoroughly during the neonatal period or before discharge of preterm infants so that iron supplementation can be individualized.